Comparison of fungiform taste‐bud distribution among age groups using confocal laser scanning microscopy in vivo in combination with gustatory function. (25th February 2016) - Saito, Takehisa; Ito, Tetsufumi; Ito, Yumi; Manabe, Yasuhiro; Sano, Kazuo
Abstract : The aim of this study was to compare the distribution of taste buds in fungiform papillae (FP) and gustatory function between young and elderly age groups. Confocal laser scanning microscopy was used because it allows many FP to be observed non‐invasively in a short period of time. The age of participants ( n = 211) varied from 20 to 83 yr. The tip and midlateral region of the tongue were observed. Taste buds in an average of 10 FP in each area were counted. A total of 2, 350 FP at the tongue tip and 2, 592 FP in the midlateral region could be observed. The average number of taste buds was similar among all age groups both at the tongue tip and in the midlateral region. The taste function, measured by electrogustometry, among participants 20–29 yr of age was significantly lower than that in the other age groups; however, there was no difference among any other age groups in taste function. These results indicate that the peripheral gustatory system is well maintained anatomically and functionally in elderly people.